How neighbourhood interactions control the temporal stability and resilience to drought of trees in mountain forests. (18th November 2019) - Jourdan, Marion; Kunstler, Georges; Morin, Xavier
Abstract: Over the coming decades, the predicted increase in frequency and intensity of extreme events such as droughts is likely to have a strong effect on forest functioning. Recent studies have shown that species mixing may buffer the temporal variability of productivity. However, most studies have focused on temporal stability of productivity, while species mixing may also affect forest resilience to extreme events. Our understanding of mechanisms underlying species mixing effects on forest stability and resilience remains limited because we ignore how changes from intraspecific to interspecific interactions in the neighbourhood of a given tree might affect its stability and resilience to extreme drought (i.e. response during and after this drought). This is crucial to better understand forests' response to climate change and how diversity may help maintain forest functioning. Here we analysed how local intra‐ or interspecific interactions may affect the temporal stability and resilience to drought of individual trees in French mountain forests, using basal area increment data over the previous 20 years for Fagus sylvatica, Abies alba and Quercus pubescens . We analysed the effect of interspecific competition on (a) the temporal stability and (b) the resilience to drought (resistance and recovery) of individual tree radial growth. We found no significant interspecific competition effect on temporal stability, but species‐specific effects on tree growth resilience to drought. There was a positive effect of heterospecific proportion on the drought resilience of Q. pubescens, a negative effect for A. alba and no effect for F. sylvatica. These differences may be related to interspecific differences in water use or rooting depth. Synthesis: In this study, we showed that stand composition influences individual tree growth resilience to drought, but this effect varied depending on the species and its physiological responses. Our study also highlighted that a lack of biodiversity effect on long‐term stability might hide important effects on short‐term resilience to extreme climatic events. This may have important implications in the face of climate change. Abstract : Here, we showed that stand composition influences individual tree growth resilience to drought, but this effect varied depending on the species and its physiological responses. Our study also highlighted that a lack of biodiversity effect on long‐term stability might hide important effects on short‐term resilience to extreme climatic events. This may have important implications in the face of climate change. Foreign Language Abstract Resume: Au cours des prochaines décennies, l'augmentation de la fréquence et de l'intensité des événements extrêmes, tels que les sécheresses, aura probablement un fort effet déstabilisateur sur les écosystèmes forestiers. Récemment, des études ont montré que le mélange d'espèces pourrait tamponner l'effet du stress sur les processus forestiers. La grande majorité des études mettent l'accent sur l'effet du mélange sur la stabilité temporelle des écosystèmes, mais le mélange pourrait également affecter la résilience des forêts aux sécheresses. De plus, notre compréhension des mécanismes sous‐jacents reste encore limitée et peu d'études permettent de les démêler. Pourtant cette compréhension est crucial pour mieux appréhender la réaction des forêts au changement climatique et comment la diversité peut aider à maintenir leur fonctionnement. Nous analysons ici comment les interactions intra ou interspécifiques locales affectent la stabilité temporelle et la résilience à la sécheresse des arbres individuels dans les forêts de montagne avec des séries d'accroissement en surface terrière (BAI) de hêtres ( Fagus sylvatica [L.]), de sapins ( Abies alba [L.]) et de chênes ( Quercus pubescens [L.]). Nous avons analysé l'effet de la compétition interspécifique sur la stabilité temporelle individuelle et les deux dimensions de la résilience à la sécheresse: la résistance et la récupération. Nous n'avons trouvé aucun effet significatif de compétition interspécifique sur la stabilité temporelle. Par contre nous avons pu constater un effet positif de la compétition hétérospecifique sur la résilience du chêne, négatif sur celle du sapin et pas d'effet pour le hêtre. Les différences entre les espèces pourraient être dues à leurs différences de stratégies hydriques. Dans cette étude, nous avons montré que la composition du peuplement influe sur la résilience de la croissance des arbres face à la sécheresse, et que cet effet varie avec l'espèce. Nous avons également mis en lumière le fait que l'absence d'effet de la biodiversité sur la stabilité à long terme pourrait masquer des effets importants sur la résilience à court terme aux événements climatiques extrêmes. Cela pourrait avoir des implications importantes face au changement climatique.